2011
DOI: 10.1002/car.1100
|View full text |Cite
|
Sign up to set email alerts
|

A rapid systematic review on the association between childhood physical and sexual abuse and illicit drug use among males

Abstract: This paper aims to review studies in relation to the association between childhood physical (CPA) and sexual abuse (CSA) and illicit drug use among the male clinical and general community populations using a systematic approach. Primary studies were identifi ed using online databases which were searched comprehensively using a set of pre-determined search criteria and terms. Other sources included expert contact and the reference list of a relevant review. Associations between exposure (CPA/CSA) and outcome (i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 49 publications
(93 reference statements)
1
22
1
Order By: Relevance
“…Indeed, a recent study by Spinazzola and colleagues (2014) identified that psychological maltreatment accounts for a significant proportion of the variance in mental health outcomes for youth, above and beyond effects of physical and sexual abuse and thus, should be considered along with measures of physical and sexual abuse. In sum, given the multiple dimensions of maltreatment, the frequent overlap between maltreatment types, and the varied findings regarding how maltreatment type relates to outcomes in youth, a broad, more-inclusive approach to conceptualization of maltreatment that accounts for other dimensions (such as severity and chronicity) to use when examining the path between maltreatment and outcomes is warranted (Butt et al, 2011; English, Upadhyaya, et al, 2005). …”
Section: Measurement Problems Associated With Dimensions Of Maltreatmentmentioning
confidence: 99%
“…Indeed, a recent study by Spinazzola and colleagues (2014) identified that psychological maltreatment accounts for a significant proportion of the variance in mental health outcomes for youth, above and beyond effects of physical and sexual abuse and thus, should be considered along with measures of physical and sexual abuse. In sum, given the multiple dimensions of maltreatment, the frequent overlap between maltreatment types, and the varied findings regarding how maltreatment type relates to outcomes in youth, a broad, more-inclusive approach to conceptualization of maltreatment that accounts for other dimensions (such as severity and chronicity) to use when examining the path between maltreatment and outcomes is warranted (Butt et al, 2011; English, Upadhyaya, et al, 2005). …”
Section: Measurement Problems Associated With Dimensions Of Maltreatmentmentioning
confidence: 99%
“…Compared to adults, adolescents who drink alcohol to excess may be more at risk because they drink in the company of inexperienced peers who may not act appropriately to aid or protect those who become dangerously intoxicated. The risks can be presumed to be increased for adolescents who begin this behavior at very young ages, and at least six studies have noted a younger age of initiation of substance use for adolescents with histories of childhood maltreatment, compared to those without such histories (Tonmyr et al 2010; also see Butt et al 2011). For example, Hamburger et al (2008) asked nearly 4,000 students from a high risk district about their experiences before the age of 10 years of witnessing intimate partner violence, and experiencing either sexual abuse or injury-causing physical abuse.…”
Section: Substance Abuse and Adolescent Health Developmentmentioning
confidence: 99%
“…However, given that many young people who use marijuana also use other substances (Macleod et al 2004) and given difficulties in studying effects of specific drugs in poly-substance using groups, a recent systematic review found "no strong evidence that use of cannabis in itself has important consequences for psychological or social health" of young people, although effects cannot be ruled out (Macleod et al 2004(Macleod et al , p. 1586. Others have noted the difficulties in drawing conclusions given that substance use is complex and multifaceted (Butt et al 2011). Similarly, Schweinsburg et al (2008) noted that persistence of deficits beyond 6 weeks of cannabis abstinence has not been established, and that potential pre-existing differences between heavy users and non-or light users might contribute to short-term observed differences.…”
Section: Substance Abuse and Adolescent Health Developmentmentioning
confidence: 99%
“…Makaruse (2010) defines substance abuse as taking too much of a drug, taking a drug too often or taking drugs or substances for wrong reasons. Houston, et al (2012); Butt et al (2011) observed that there is a close relationship between childhood sexual abuse and illicit of substance abuse among people including those in street situations. Therefore, this paper examines the multilayered or complex relationship between masturbation and substance abuse among the street children of Harare Central Business District.…”
Section: Introductionmentioning
confidence: 99%